PENGARUH RELASI KONSUMEN DAN WORD OF MOUTH TERHADAP LOYALITAS NASABAH BANK BPD BALI CABANG BADUNG - Indra Saputra, Ida Bagus; Suryani, Alit; Nurcahya, I Ketut (E-Jurnal Manajemen; Vol 4 No 3 (2015), 2015)
Loyalty is a target to be achieved as a key to business success. Map of banking competition in Indonesia is increasingly squirm, Banks are required to provide customer satisfaction and establish communication that will ultimately create loyalty. Bank BPD Bali as a local commercial bank in Bali not also can escape from the threats of competitions. This research was conducted at the Regional Branch Bali Badung, samples taken 100 customers with purposive sampling methods. The analysiss techniqueds useds is multipled linear regressions. These results indicate that the variable customer relations and word of mouth positive and significant effect on customer loyalty Branch BPD Bali Badung. This suggests that consumer relations and word of mouth can increase customer loyalty, therefore BPD Bali Badung Branch should maintain and improve the quality of communication that has been well maintained and give a gift or bonus for those who are loyal. Keyword: Relationship Consumen, Word of Mouth and Consumen Loyalty